DNA as template and P-source for synthesis of Co2P/Co2N core–shell nanostructure embedded in N-doped carbon nanofiber derived from electrospun precursor for oxygen evolution reaction. (20th January 2021) - Li, Huizhen; Kong, Xiaoxing; Geng, Xinhua; Gu, Caiqin; Liu, Zili; Wang, Jiahai
Abstract: In this work, a typical electrospinning technology and subsequent calcination is developed for fabrication of Co2 P/Co2 N core–shell nanostructure embedded in N-doped carbon nanofiber (Co2 P/Co2 N@CNF-DNA(C)) for oxygen evolution reaction, where DNA is used as template and P-source. In such unique nanostructure, (1) the synergistic interaction between Co2 P and Co2 N in the core–shell nanostructure optimizes the electron interaction, thus reducing the energy barrier; (2) the binding effect of DNA reduces the charge transfer resistance and improve the stability of the obtained materials, the base sequence of DNA also has significantly effect on the electric catalytic performance; (3) the porous conductive carbon nanofiber matrix provides more exposures of reaction sites, thus enhancing electrolyte penetration and facilitates the release of O2 bubbles. In view of these advantages, the Co2 P/Co2 N@CNF-DNA(C) nanofiber shows a remarkable OER catalytic performance and prominent electrochemical stability, outperforming those of the Co2 N@CNF as well as its many counterparts. Therefore, the typical electrospinning followed by calcination strategy in which DNA used as template and P-source pave a way to synthesize other transition metal phosphides electrocatalysts in the future.